2014
DOI: 10.1007/s11248-014-9850-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts on the metabolome of down-regulating polyphenol oxidase in potato tubers

Abstract: Tubers of potato (Solanum tuberosum L. cv. Estima) genetically modified to reduce polyphenol oxidase (PPO) activity and enzymatic discolouration were assessed for changes in the metabolome using Liquid Chromatography-Mass Spectrometry (LC-MS) and Gas Chromatography (GC)-MS. Metabolome changes induced over a 48 hour (h) period by tuber wounding (sliced transverse sections) were also assessed using two PPO antisense lines (asPPO) and a wild-type (WT) control. Data were analysed using Principal Components Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Additionally, silencing the walnut PPO genes via RNA interference technology reportedly increases the chances that the resulting plants develop necrotic plaques [8]. Many other studies have confirmed the relationship between PPOs and plant defense [9,10,11,12,13,14,15,16,17]. Studies regarding the overexpression or silencing of PPO genes have clearly demonstrated the key role of PPOs in plant defense responses.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, silencing the walnut PPO genes via RNA interference technology reportedly increases the chances that the resulting plants develop necrotic plaques [8]. Many other studies have confirmed the relationship between PPOs and plant defense [9,10,11,12,13,14,15,16,17]. Studies regarding the overexpression or silencing of PPO genes have clearly demonstrated the key role of PPOs in plant defense responses.…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase is a copper containing enzyme present in both plant and animal tissues that catalyzes the production of melanin and other pigments from tyrosine by oxidation. A typical illustration is the blackening of a peeled or sliced tuber crop, during exposure to air [5]. From a mechanistic perspective, tyrosinases oxidize their substrates through hydroxylation of monophenol to o-diphenol (monophenolase or cresolase activity) and the oxidation of diphenol to o-quinones (diphenolase or catecholase activity), both using molecular oxygen, followed by a series of non-enzymatic steps, which may result in the formation of melanin [6].…”
Section: Introductionmentioning
confidence: 99%
“…In potatoes, the losses by mechanical injuries occur during every stage of production, from harvest to consumption. However, as the injuries are cumulative, the whole process should be monitored, and there should be actions to prevent damages (Shepherd et al, 2015). Ferreira and Netto (2007) reported that in potatoes the superficial damages and internal bruising can get to 40% of the whole production, reducing the sale price and even causing the rejection of the product.…”
Section: Introductionmentioning
confidence: 99%